The thermal and storage stability of bovine haemoglobin by ultraviolet-visible and circular dichroism spectroscopies - Ruchir Bhomia; Vivek Trivedi; Nichola J. Coleman; John C. Mitchell (Elsevier, 2016)
The effects of temperature, pH and long-term storage on the secondary structure and conformation changes of bovine haemoglobin (bHb) were studied using circular dichroism (CD) and ultraviolet--visible (UV-vis) spectroscopies. Neural network software was used to deconvolute the CD data to obtain the fractional content of the five secondary structures. The storage stability of bHb solutions in pH 6, 7 and 8 buffers was significantly higher at 4 °C than at 23 °C for the first 3 days. A complete denaturation of bHb was observed after 40 days irrespective of storage temperature or pH. The bHb solutions were also exposed to heating and cooling cycles between 25 and 65 °C and structural changes were followed by UV-vis and CD spectroscopies. These experiments demonstrated that α-helix content of bHb decreased steadily with the increasing temperature above 35 °C at all pH values. The loss in α-helicity and gain in random coil conformations was pH-dependent and the greatest under alkaline conditions. Furthermore, there was minimal recovery of the secondary structure content upon cooling to 25 °C. The use of bHb as a model drug is very common and this study elucidates the significance of storage and processing conditions on its stability.